Illness related wage and productivity losses: Valuing 'presenteeism'. (December 2015) - Zhang, Wei; Sun, Huiying; Woodcock, Simon; Anis, Aslam
Abstract: One source of productivity loss due to illness is the reduced "quantity" or "quality" of labor input while working, often referred to as presenteeism. Illness-related presenteeism has been found to be potentially more costly than absenteeism. To value presenteeism, existing methods use wages as a proxy for marginal productivity at the firm level. However, wage may not equal marginal productivity in some scenarios. One instance is when a job involves team production and perfect substitutes for workers are not readily available. Using a Canadian linked employer-employee survey (2001–2005), we test whether relative wage equals relative marginal productivity among team workers and non-team workers with different frequencies of presenteeism (reduction at work due to illness). For the pooled cross-sectional estimates (2001, 2003, 2005) we obtain 13, 755 observations with 6842 unique workplaces. There are 6490 observations for the first differences estimates from the odd years and 5263 observations for the first differences estimates from 2001 to 2002 and 2003 to 2004. We find that in both small and large firms, team workers with frequent reductions at work are less productive but earn similarly compared with non-team workers without reductions. We also find that in small firms, workers with occasional work reductions are more productive than workers without reductions, but the reverse is true in large firms. The study findings partially support the literature stating that productivity loss resulting from employee presenteeism could exceed wages if team work is involved. Highlights: Wages are commonly used as a proxy for marginal productivity to value presenteeism. Employee self-reported presenteeism is linked to employers' production and payroll. We test the equality of wage and marginal productivity with regard to presenteeism. Productivity losses due to frequent presenteeism of team workers exceed wages.